Map of glacial geology, Glenlyon area, Yukon Territory: Supplement 1 from "Continental glaciation in the Glenlyon area, Pelly River District, Yukon, Canada" (Thesis) - Campbell, Richard Bradford (CaltechDATA, 1951)
The Glenlyon area in central Yukon is bounded by 62° and 63°N and 134° and 136°W. It is part of the Yukon Plateau, a mature upland surface surmounted by isolated peaks and small ranges, and dissected by deep, young valleys. Features of glacial erosion and deposition ore such that the direction of flow and the upper limit or the last glaciation can be determined from them. Ice flowed into central Yukon from three sources, Selwyn Mountains to the east, Cassiar mountains to the southeast, and the Coast and St. Elias mountains to the south. Ice moved into the Glenlyon area from the first two of these sources and apparently the maximum stages of these two gla cial advances were not synchronous, but Selwyn ice was active last. In this area, many higher mountains and hills projected above the ice surface as nunataks. In detail, topography altered the direction of ice flow, ice thickness and extent. Evidence from adjacent parts of Yukon suggest two or possibly three glaciations but only the last has been recognized in the Glenlyon area although this could not have escaped glaciation in earlier stages. The large glaciers of central Yukon developed by windward building in contrast with the Cordilleren ice sheet in central British Columbia which developed on the lee of the Coast Range.